Experimental study of the bending of a soft bar - Yeo, Matthew Chee Yean (Nanyang Technological University, 2024)
Soft materials are of great interest in the present day as they prove useful in many industries, like the medical field or space exploration. As new materials or variations of materials are created, it may prove challenging to obtain its physical properties. Mathematical models can be formulated to aid in predicting the behaviour of the new materials. This project utilizes the MATLAB curve fitting toolbox to assess the goodness of fit of different models on the deflection of soft agar beams, while varying factors such as concentration, depth, and load. Other areas explored include failure load and defect testing of the beams. Sum of squares due to error and adjusted -squared metrics were employed to compare the models. The nonlinear nature of agar lends itself to the use of higher order polynomial models for the interpolation of data. It was discovered that both quadratic and exponential models have merits and shortcomings in extrapolating data and must be selected carefully for this use.